Free light chain and intact immunoglobulin abnormalities in heart transplant recipients: Two year follow-up timelines and clinical correlations - Sečník, Peter; Lavríková, Petra; Hošková, Lenka; Malíková, Pavlína; Jabor, Antonín; Franeková, Janka (Transplant immunology, 2017)
OBJECTIVES: To assess the timelines of serum free light chain (sFLC) concentrations and the kappa/lambda light chain (K/L) ratio in heart transplant (HTX) recipients. To analyze the performance of serum protein electrophoresis (SPE), serum immunofixation (sIFE) and sFLC measurements for gammopathy detection following a HTX. METHODS: A total of 96 patients who underwent a HTX were analyzed during a two-year follow-up period. The relevant clinical data were obtained from patient medical records. SPE, sIFE and sFLC methods were used for the detection of free light chain and intact immunoglobulin gammopathies at 4 time points after HTX. RESULTS: A statistically significant decrease in sFLC K and L (a decrease of 39.1% and 27.6%, respectively, when compared to pretransplant values) was found 9months after the HTX (p<0.001, Friedman test). We detected SPE or sIFE abnormalities in 23 (8.4%) samples, and sFLC K/L ratio abnormalities in 34 (12.4%) samples. All of the K/L ratio abnormalities had normal SPE/sIFE values, and 19% of the findings were persistent. CONCLUSIONS: A significant and consistent dynamics in the sFLC concentration was found in the HTX patients during a 2-year follow-up period, which reflected changes in the immunosuppressant dosage. A remarkable number of monoclonal and polyclonal gammopathies was identified with some persistent abnormalities, using the SPE/sIFE and sFLC methods. Some of the detected abnormalities, which might possess a higher risk for PTLD if interpreted according to common practice in nonTX patients can only be detected by sFLC methods.
Keywords: Humans; transplantace srdce; lidé středního věku; Electrophoresis; Free light chains; Immunofixation; následné studie; Female; Aged; dospělí; senioři; lidé; Heart Transplantation; Posttransplant lymphoproliferation; Immunoglobulin kappa-Chains; Immunoglobulin lambda-Chains; Adult; imunoglobuliny - lambda-řetězce; ženské pohlaví; Male; Middle Aged; Heart transplantation; mužské pohlaví; Follow-Up Studies; imunoglobuliny - kappa-řetězce